Improving the Lives of Teachers in the Early Care and Education Field to Better Support Children and Families. Issue 3 (22nd May 2019) - Cassidy, Deborah J.; Lippard, Christine; King, Elizabeth K.; Lower, Joanna K.
Abstract : The future of healthy families demands highly capable external supports. Early care and education, particularly early care and education teachers, are well positioned to support families. However, early care and education teachers are faced with challenges to their own well‐being and that of their own families. Barriers to teacher well‐being include low compensation, lack of support for education and professional development, and a larger societal context that often devalues and inadequately supports the profession. The future of healthy families can be bolstered by addressing early care and education teacher well‐being—specifically wages, work environment, and professionalism—and increasing support for high‐quality early care and education from community and societal systems.